A prebiotic matrix for encapsulation of probiotics: physicochemical and microbiological study. (2nd January 2016) - Atia, Abdelbasset; Gomaa, Ahmed; Fliss, Ismail; Beyssac, Eric; Garrait, Ghislain; Subirade, Muriel
Abstract: This work aims to develop an encapsulated oral-synbiotic supplement by studying the effect of adding inulin in alginate beads and observing its ability to protect three probiotic strains: Pediocucus acidilactici, Lactobacillus reuteri and Lactobacillus salivarius . Beads of different inulin concentrations 0%, 5%, 10%, 15% and 20% (w/v) in 2% (w/v) alginate solution were prepared by the extrusion/ionotropic gelation method. Polymer distribution within beads was characterised using confocal laser scanning microscopy. Interactions between alginate and inulin were monitored by Fourier transform infra-red spectroscopy (FTIR). Effect of encapsulation on viability, antimicrobial ability, acid tolerance and bile tolerance of probiotic strains were investigated. Antimicrobial and probiotic properties of bacterial strains were not affected by encapsulation. Bacterial protection against acidity was increased by adding inulin. Beads with 5% w/v inulin were the most effective in bacterial protection against bile-salts. To our knowledge, this work is the first to use such high concentrations of inulin.